Structurally Different Calcium(II) Complexes with 5‐Substituted Tetrazole Ligands1. Issue 4 (2nd February 2016) - Liu, Qiao; Zhao, Li Yang; Lu, Yi Ming; Yue, Qiu Yan; Zhang, Fei Fei; Wei, Bo; Li, Qiao Yun; Yang, Gao Wen
Abstract: Three different tetrazole‐carboxylate ligands, Hpymtza, Hpytza, and H2 dtzeda were chosen to be reacted with Ca(NO3 )2 · 4H2 O, resulting in the formation of three coordination compounds, [Ca(pymtza)2 (H2 O)4 ] (1 ), [Ca(pytza)2 (H2 O)2 ] (2 ), and [Ca(dtzeda)(H2 O)2 ] (3 ) [Hpymtza = 5‐(2‐pyrimidyl)tetrazole‐1‐acetic acid, Hpytza = 5‐(3‐pyridyl)tetrazole‐2‐acetic acid, and H2 dtzeda = 1, 2‐bis(tetrazol‐5‐yl)ethane‐N1, N1′‐diacetic acid]. X‐ray diffraction analysis revealed that compound1 displays a mononuclear structure, compound2 is a one dimensional zigzag chain structure, whereas3 shows a three‐dimensional structure. The structures were controlled by not only the different substituents of the tetrazolyl ring, but also the complementary hydrogen bonds. Furthermore, the luminescence properties of compounds1 –3 were investigated at room temperature in the solid state. These emissions can be tentatively attributed to the ligand centered emission. Abstract :